PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SD. - Arisna, Putri; Herpratiwi; Dian Putra, Agung; Nurwahidin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study was the low learning outcomes in IPAS of fourth-grade students at SD Negeri 3 Perumnas Way Kandis. This study aimed to determine the effect of the implementation of the Problem Based Learning (PBL) model assisted by audio-visual media in the form of animated videos on IPAS learning outcomes, the effect of the implementation of the PBL model assisted by audio-visual media in the form of sound slides on IPAS learning outcomes, and the difference in effects between the implementation of the PBL model assisted by animated videos and sound slides on the IPAS learning outcomes of fourth grade elementary school students. This study employed a quantitative approach with a quasi-experimental design, namely a non-equivalent control group design. The population in this study consisted of all fourth-grade students, and the sampling technique used was non-probability sampling. Data were collected through learning outcome tests, while data analysis was conducted using paired sample t-tests and independent sample t-tests. The results showed that the implementation of the PBL model assisted by audio-visual media in the form of animated videos had an effect on IPAS learning outcomes. The implementation of the PBL model assisted by audio-visual media in the form of sound slides also had an effect on IPAS learning outcomes. In addition, there was a difference in the effects between the use of the PBL model assisted by animated videos and sound slides on students IPAS learning outcomes.